Development of a novel constitutive model incorporating phase transformation and dynamic recrystallization effects for laser-assisted machining of Ti6Al4V alloy - Binbin Xu; Xin Liu; Hongguang Liu; Shijia Shi; Yuyang Tang; Jun Zhang (Journal of Materials Research and Technology)
Laser-assisted machining (LAM) has emerged as a versatile technique for processing difficult-to-machine materials—such as titanium alloys and nickel-based alloys—with broad implications for advanced manufacturing and cross-disciplinary engineering applications. In this study, we propose a novel constitutive model for Ti6Al4V that integrates phase transformation (PT) and dynamic recrystallization (DRX) effects to capture the extreme thermo-mechanical conditions encountered during LAM. The model is calibrated using high-temperature, high-strain-rate stress–strain data obtained from Split Hopkinson Pressure Bar (SHPB) experiments and is based on the JC–TANH framework. It is implemented within a finite element environment to simulate the complete LAM process, encompassing both the cutting and cooling stages. Experimental validation demonstrates that the model accurately predicts cutting forces, serrated chip formation, PT volume fractions, and grain refinement. These results not only enhance our theoretical understanding of microstructural evolution under extreme conditions but also provide practical guidelines for optimizing machining parameters in high-performance manufacturing systems.